Reverse logistics: RFID the key to optimality - Rezwan Asif (Journal of Industrial Engineering and Management (JIEM), 2011)
Purpose: The purpose of this paper is to find ways to reduce uncertainties in Reverse logistic supply chain (RLSC) through the use of Radio-frequency identification (RFID) technology.Design/methodology/approach: This paper reviews literature and builds model to relate RFID with uncertainties in order to optimize Reverse Logistics. Findings: RFID is really efficient to determine and detect quantity, variety and cycle times of returns; however it's not as convenient to determine quality of the returns. The collected information from RFID can be used to standardize the RLSC. Research limitations: Though it's several and unique advantages some limitations of RFID have been identified in quality and processing sequence, collecting points and different standards, and in global usage. Originality/value: Previous studies in the area of Reverse Logistics and RFID don't cover all impacts of this technology on RLSC. This review paper has investigated these impacts and offers a model for optimizing the Reverse Logistics Supply Chain.
Keywords: 650; reverse logistics; RFID; uncertainties; closed-loop supply chai